Outcomes and factors associated with medical treatment failure in patients with spinal epidural abscess: A 14-year experience - María García de Santos; Jorge Calderón-Parra; Andrea Gutiérrez-Villanueva; Itziar Diego-Yagüe; Noemí Lomillos Prieto; Oscar Gil de Sagredo del Corral; Ana Fernández-Cruz; Antonio Ramos-Martínez; Elena Muñez-Rubio (PLoS ONE, 2026)
Background The optimal therapeutic approach for treating spinal epidural abscesses (SEAs) is not well defined. This study aimed to describe the failure rate of medical management and identify factors associated with failure. Methods We conducted a single-centre retrospective cohort including all adult patients diagnosed with SEA between 2009 and 2022. The primary endpoint was a composite of in-hospital mortality and motor neurological sequelae at discharge. Results Among 76 patients, 22.4% (n = 17) received initial intervention, while 77.6% (n = 59) received medical management. Among medically managed patients, 42.5% (n = 25) experienced treatment failure, and 27.1% (n = 16) required salvage surgery. Factors associated with treatment failure included diabetes mellitus (32.0% vs 8.8%, p = 0.040), an erythrocyte sedimentation rate (ESR) greater than 75 mm/h (66.7% vs 31.0%, p = 0.021), methicillin-resistant Staphylococcus aureus (MRSA) (28.0% vs 0%, p < 0.001) and anterior epidural involvement (91.3% vs 60.6%, p = 0.014). Although patients initially treated surgically had significant worse neurological motor situation at presentation than those managed medically (ASIA A or B 20.0% vs 3.4%), the primary endpoint occurred more frequently in patients with failure of initial medical treatment than in those initially operated (65.0% vs 35.3%, p = 0.035). SEA-related mortality was also higher among those with medical treatment failure (16.0% vs 0%, p = 0.038). Conclusions Failure of medical management of SEA was common and could lead to worse outcomes. Diabetes mellitus, ESR greater than 75 mm/h, MRSA, and ventral epidural involvement were associated with failure. Initial surgery might be considered for low operative risk patients in the presence of these factors. Prospective trials are needed to better guide initial management strategies.